A non-proteolytic role for ubiquitin in deadenylation by the RNA-binding E3 ligase MEX-3C - Cano, Florencia; Rapiteanu, Radu; Winkler, G.S.; Lehner, Paul J. (Nature Publishing Group, 2015)
The regulation of protein and mRNA turnover is essential for many cellular processes. We recently showed that ubiquitin—traditionally linked to protein degradation—directly regulates the degradation of mRNAs through the action of a newly identified family of RNA-binding E3 ubiquitin ligases. How ubiquitin regulates mRNA decay remains unclear. Here, we identify a new role for ubiquitin in regulating deadenylation, the initial and often rate-limiting step in mRNA degradation. MEX-3C, a canonical member of this family of RNA-binding ubiquitin ligases, associates with the cytoplasmic deadenylation complexes and ubiquitinates CNOT7(Caf1), the main catalytic subunit of the CCR4-NOT deadenylation machinery. We establish a new role for ubiquitin in regulating MHC-I mRNA deadenylation as ubiquitination of CNOT7 by MEX-3C regulates its deadenylation activity and is required for MHC-I mRNA degradation. Since neither proteasome nor lysosome inhibitors rescued MEX-3C-mediated MHC-I mRNA degradation, our findings suggest a new non-proteolytic function for ubiquitin in the regulation of mRNA decay.